The immunologic balance: three cases of rituximab-associated melanoma. Issue 1 (15th November 2021) - Davidson, Tara M.; Markovic, Svetomir N.; Dimou, Anastasios
Abstract : Currently, there is no known clinical evidence that rituximab increases the rate of subsequent primary malignancies; however, some studies have raised the question of increased melanoma risk following rituximab treatment for non-Hodgkin lymphoma. We report three interesting cases of suspected rituximab-induced melanoma. We hypothesize that this association is secondary to rituximab-driven shifts in the immunologic balance. Based on these cases, it is possible that the number of post-rituximab melanoma cases is underreported. Further mechanistic research into individual cases and population-level studies are required to better define association and risk; however, given the increasing prevalence of oncologic and nononcologic rituximab use, awareness across all fields is essential.